The physicochemical composition of honey from Indonesian stingless bee (Tetragonula laeviceps) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Agussalim, Umami N, Nurliyani, Agus A. 2021. The physicochemical composition of honey from Indonesian stingless bee (Tetragonula laeviceps). Biodiversitas 22: 3257-3263. The demand of honey has recently increased significantly, but this situation is widely used by irresponsible humans who made a fake honey. This present study aims to evaluate the quality based on the physicochemical composition of honey from Indonesian stingless bee Tetragonula laeviceps. Honey was obtained from three geographical origins in Indonesia, i.e. Sleman, Gunungkidul, and Lombok. The physicochemical composition of honey was analyzed such as moisture, ash, protein, pH, glucose/moisture ratio, and electrical conductivity, and amino acids. The results showed that the geographical origins had a highly significant effect (P
Keywords: Klanceng honey; nectar; pollen; adulteration; LC-MS/MS